A review on current injection techniques for low-voltage ride-through and grid fault conditions in grid-connected photovoltaic system. (1st September 2020) - Hassan, Z.; Amir, A.; Selvaraj, J.; Rahim, N.A.
Abstract: In order to meet the increasing energy demands of the modern-day world, the shift towards renewable energy has proved to be a viable alternative, as it has significantly reduced reliance on conventional energy resources. Solar energy, in particular, remains one of the best available renewable energy options, as it is abundant, clean and reliable. Owing to the susceptibility of grid-connected photovoltaic (GCPV) system against grid faults, conventionally the PV inverter would disengage from the power grid by utilizing an anti-islanding technique. Nevertheless, many countries have now implemented grid codes (GCs) to secure and regulate the operation of the GCPV systems from exposure to grid faults. Modern advanced technologies have equipped the PV inverters with the low-voltage ride-through (LVRT) capability to address the issue of grid faults and prevent equipment failure, as it develops compliance of the GCPV systems with the GCs. This paper presents an overview of inverter topologies which include the power processing stage, transformer and transformerless inverter, multilevel inverter, soft and hard switching, bidirectional and hybrid inverters. Thereafter, current injection techniques with LVRT control strategy are discussed and examined. Such techniques have been classified under four main categories: the current compensation controls, reactive current injection (RCI), linear current controls and non-linear current controls. In addition, a comparative analysis has been presented, by thoroughly discussing the merits and demerits of these control schemes, based on the performance parameters of complexity, stability, robustness and power quality assessment.